The moderating effect of celebrity endorsement on the relationship among perceived value, user interaction satisfaction, and buying behavior amongst Lazada consumers from DLSU RVR-COB ID 119 undergraduate students - Chua, Tiffany Mae Cu (Animo Repository, 2022)
The COVID-19 pandemic caused substantial changes in several factors that affected the performance of e-commerce businesses, which prompted the researchers to look at certain variables that may have had an impact on Lazada's success. Thus, the researchers made the decision to investigate how Lazada customers' perceived value and user interaction satisfaction affect their buying behavior with the influence of celebrity endorsement, acting as a moderator. In this study, perceived value will be used to identify whether Lazada Consumers’ perception towards needs and wants are satisfied by Lazada’s offered goods and services and the usage of its Mobile Application. User interaction satisfaction, the second independent variable, will be used to describe the emotional response, sentiments, and attitudes based on an overall evaluation of expectations of Lazada consumers who believe they had a positive experience using the app. Furthermore, buying behavior, the study’s dependent variable, was defined as the process through which Lazada consumers undergo, considering their requirements, reasoning, and desire as well as the order of making a purchase. Finally, celebrity endorsement will act as a moderator to determine whether Lazada’s usage of celebrity endorsements influences consumer buying behavior given the two independent variables. The sample size for the quantitative data consists of 275 RVR-COB DLSU Lazada customers. Quantitative tools used are frequency distribution tables, bar graphs, mean explanations, Cronbach's Alpha, Pearson's Correlation, Simple and Multiple Linear Regression, and Moderated Regression. Moreover, the researchers gathered qualitative data by interviewing 2 Lazada sellers, which are used in pattern matching. Overall, results suggest that perceived value and user interaction satisfaction have a significant positive effect on buying behavior. Additionally, results show that the moderating effect of celebrity endorsement is significant in the association between user interaction satisfaction and buying behavior. However, it has been found that the moderating effect of celebrity endorsement between perceived value and buying behavior is insignificant. Keywords: Perceived Value; User Interaction Satisfaction; Buying Behavior; Celebrity Endorsement; Moderated Regression; Multiple Regression